CLINICAL CHARACTERISTIC OF ADRENAL INCIDENTALOMA FROM 2010 TO 2020 IN HOSPITAL PUTRAJAYA - Goh, KG; Vergis, M; Mohamad, M; Noor, N Mohd; Hussein, Z (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Adrenal incidentaloma are lesions found incidentally on imaging. With widespread use of imaging in clinical practice, the incidence has increased. We describe the clinical characteristics of adrenal incidentaloma in an endocrine referral hospital in Putrajaya, Malaysia. METHODOLOGY This was a retrospective study reviewing medical records for adrenal lesions discovered for non-adrenal imaging from January 2010 to January 2020. Data for demographic, radiological characteristics, hormonal functionality and histopathology data were collected and analysed. RESULTS There were 164 identified patients, of which 100 (61%) were female. Site involvement was most frequent on the left (51.2%), followed by the right (40.2%); a few had bilateral lesions (8.5%). It was mostly seen in Malays (59.8%). Non-functioning adenoma was the most common diagnosis (78.1%). Among functioning adenomas, phaeochromocytoma incidence was highest (5%). The incidences of primary aldosteronism and Cushing’s syndrome were similar (1.3%). Adrenal cortical carcinoma (ACC), adrenal metastasis and lymphoma were seen in 8.1%. ACC tended to occur between ages 40 to 49 years, whereas adrenal metastases were seen in older age groups. Functioning adenomas were spread out between ages 40 to 69 years. ACC were typically more than 4 cm at detection. Functioning adenomas varied in sizes: 74.8% of non-functioning adenomas measured 1 to 3.9 cm, and 15.1% were more than 4 cm. Hounsfield units for all functioning adenomas and ACC were >20 and varied in non-functioning adenoma. CONCLUSION Adrenal incidentaloma requires further assessment as the incidence of functional tumour or malignancies were seen in up to 20%. Clinicians should have a high index of suspicion when encountering any suspected adrenal lesions. Early referral to centres that provide investigation and management of adrenal incidentaloma should be made.